Implementasi Persamaan Diferensial Model Logistik untuk Prediksi Pertumbuhan Tingkat Pernikahan Sumatera Utara - Dinda Renata Cecilia; Fuja Nauli Pasaribu; Rafika Sari Prayetno; Rio Anggara Panjaitan; Sintia Agustina Siregar (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Forecasting the number of marriages is a prediction of marriages that will occur in the future based on current and past data. The total population of the married population is continuous, that is, its growth continues without a break. The model used for continuous population is the logistic model. This study aims to see the growth of marriage in the period 2027 using the logistic model growth. Judging from the data obtained from BPS (Central Bureau of Statistics) of North Sumatra Province from 2020 to 2023, the capacity limit (C) = . The logistic model that can be used to parameterize the marriage rate in North Sumatra province is with a value of k = -0.25019918023 with the formula .Based on the logistic model, the predicted marriage rate in North Sumatra province for 2027 is 64305.93339.